Isotopic variations of copper at the protein fraction level in neuronal human cells exposed in vitro to uranium. Issue 20 (6th September 2019) - Paredes, Eduardo; Malard, Véronique; Vidaud, Claude; Avazeri, Emilie; Ortega, Richard; Nonell, Anthony; Isnard, Hélène; Chartier, Frédéric; Bresson, Carole
Abstract : Accurate isotope ratio determination was downscaled to the level of metal-containing protein fractions obtained from cell line lysates. Abstract : The study of isotopic variations of endogenous and toxic metals in fluids and tissues is a recent research topic with an outstanding potential in biomedical and toxicological investigations. Most of the analyses have been performed so far in bulk samples, which can make the interpretation of results entangled, since different sources of stress or the alteration of different metabolic processes can lead to similar variations in the isotopic compositions of the elements in bulk samples. The downscaling of the isotopic analysis of elements at the sub-cellular level, is considered as a more promising alternative. Here we present for the first time the accurate determination of Cu isotopic ratios in four main protein fractions from lysates of neuron-like human cells exposed in vitro to 10 μM of natural uranium for seven days. These protein fractions were isolated by Size Exclusion Chromatography and analysed by Multi-Collector Inductively Coupled Plasma Mass Spectrometry to determine the Cu isotopic variations in each protein fraction with regard to the original cell lysate. Values obtained, expressed as δ 65 Cu, were −0.03 ± 0.14 ‰ ( U c, k = 2), −0.55 ± 0.20 ‰ ( U c, k = 2), −0.32 ± 0.21 ‰ ( U c, k = 2) and +0.84 ± 0.21 ‰ ( U c, k = 2) for the four fractions, satisfying the mass balance. The results obtained in this preliminary study pave the way for dedicated analytical developments to identify new specific disease biomarkers, to gain insight into stress-induced altered metabolic processes, as well as to decipher metabolic pathways of toxic elements.